Method of deformation analysis for composite structures of soils and masonry stones. (February 2017) - Hashimoto, Ryota; Kikumoto, Mamoru; Koyama, Tomofumi; Mimrua, Mamoru
Abstract: The coupled numerical manifold method (NMM) and discontinuous deformation analysis (DDA) are enhanced to simulate deformations of continuous soil and discontinuous masonry structures. An elasto-plastic NMM-DDA is formulated that incorporates elasto-plastic constitutive laws into incremental forms of the equation of motion. A node-based uniform strain element is applied to avoid volumetric locking, which often occurs in conventional NMM-DDA. The proposed method is applied to three fundamental boundary value problems: a beam bending problem, a bearing capacity problem of a footing, and a bearing capacity problem of a masonry structure. The method is verified through comparisons with conventional solutions.